Implementation of Islamic Psychology in the Formation of Student Morals and Discipline in the Dormitory Environment - Oscharil Aji Mukti; Mutohharun Jinan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This study aims to analyze the application of Islamic psychology in the formation of student morals and discipline at RUSHD Sragen Superior High School, especially in the dormitory environment. In the era of globalization, character education is an important aspect in facing increasingly complex moral and discipline challenges among students. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the application of Islamic psychology through habituation, example, and moral education based on religious values is able to increase student discipline, responsibility, and independence. Habituation of worship, the implementation of daily responsibilities, and the consistent application of rules have proven to be effective in shaping the character of students. This research also reveals the importance of the role of dormitory coaches, teachers, and parental involvement in supporting the development of students' morals and discipline. The novelty of this research lies in the integration of Islamic psychology in dormitory-based character education, especially in the formation of morals and discipline, which was still limited to being discussed in previous research. This research contributes to the development of character education programs based on Islamic psychology, especially in dormitory-based educational institutions.